Language Test Anxiety Between Gender and Proficiency Among Foreign Language Learners - Fibiyani Fibiyani; Theodesia Lady Pratiwi (IALLTEACH (Issues In Applied Linguistics & Language Teaching), 2023)
The purpose of this research was to examine the level of anxiety of students in facing an English test at Batam International University, taking into account the gender and proficiency of the students. This study wanted to find out whether there were significant differences in the level of test anxiety between the gender of students and proficiency scores, and to look for interactions between these two variables on test anxiety. This research uses a quantitative method using a survey research design. 100 learners (59 females and 41 males) became respondents to this research. The data were then analyzed using descriptive analysis. To examine significant differences and interactions between student gender and proficiency in test anxiety, Two Way Anova was used as a hypothesis testing tool. The results of this research indicate that learners at Batam International University experience and face moderate levels of test anxiety. The results of testing the hypothesis show that there is a significant difference in the level of exam anxiety between male and female students, where female students report higher levels of test anxiety (53.19) compared to male students (43.61). However, there was no significant difference in test anxiety levels among proficiency learners. In addition, there was no significant interaction between gender and proficiency in influencing the level of test anxiety among learners. Therefore, further research is needed to build stronger research on the effect of gender and proficiency on exam anxiety, and how it influences students' English test performance.